The Effect of Good Corporate Governance and Auditor Performance on Audit Quality with Integrity as a Moderating Variable - Sahidah Sahidah; Robiur Rahmat Putra; Kiko Armenita Julito (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
Good Corporate Governance or corporate govenance is a company’s effort to create a pattern of conducive ralationships between steakeholders in a company. Because a conducive relationship between these stakeholders is a prerequisite in realizing maximum company performance to support increasing company value. With the statement above, it is clear thah corporate governance is closely related to the value of a company and of course also closely related to financial performance within the company. This research goals to examine the effect of Good Corporate Governance and auditor performance on audit quality, with integrity as a moderating variable. The sample selection technique used in this study was a purposive sampling technique with 100 samples. The data collection method used is a questionnaire, by distributing questionnaires in public accounting firms (KAP). The data analysis technique used to test the hypothesis in research is Partial Least Square (PLS) analysis, which is a Structural Equation Modeling (SEM) equation model with a variance approach or a component-based structural equation model. The results of the study show that good corporate governance, auditor performance influences audit quality. And also shows that integrity is able to moderate the performance of the auditor, which will affect audit quality. On the other hand, the research results show that integrity does not moderate Good Corporate Governance on audit quality.